Studies on sodium aerosols dispersion in open environment for fast reactor safety. (March 2019) - Subramanian, V.; Kumar, Amit; Pujala, Usha; Sujatha, P.N.; Srinivas, C. Venkata; Bagavathsingh, A.; Goplakrishnan, V.; Ananthanarayanan, R.; Kumar, A. Ashok; Kumar, S. Krishna; Chandramouli, S.; Baskaran, R.; et al.
Highlights: Experimental and modelling study on sodium aerosol dispersion in environment. Determination of ground level aerosol concentration including chemical speciation and aerosol deposit. Physical and chemical characteristics of sodium aerosols transported in the atmosphere in the downwind direction. Theoretical simulations of dispersed aerosol characteristics. Abstract: In a sodium cooled Fast Reactors (SFRs), in the event of secondary sodium circuit failure (cracks developed in the fluid carrying pipe), the hot sodium is exposed to atmosphere, burns to produce sodium combustion aerosols and is released into the atmosphere. Of the released aerosols, sodium hydroxide (NaOH) poses inhalation health hazard (Threshold Limit Value (TLV) of NaOH is 2.0 ∗ 10 −6  kg/m 3 for inhalation) due to its corrosive nature. In the context of fast reactor safety analysis studies, the quantity of sodium aerosols reaching various locations in the downwind direction and its chemical composition are very important. In this study sodium aerosol dispersion experiments in the open environment were conducted, by burning 50 kg of sodium. Aerosols were released through a 10 m high chimney and sampling was done in a range of up to 700 m distance. About 100 aerosol samples were collected in a 30° field sector with 170° as a bisector line. Aerosol characteristics were measured and atmospheric dispersion simulations were performed to predict the ground level concentration and deposition using Gaussian Plume and FLEXPART models. The simulation results were compared with experimental measurements and models were validated. Both experimental results and model predictions showed that, the maximum ground level concentration occurred at 100 m distance from the release point and that the concentrations increased with increase of the release rate. About 14% of the total quantity of burnt mass of sodium was deposited as aerosols between 50 and 700 m distance. The chemical species at all the arc distances was found to be sodium bi-carbonate. The study is found useful in hazard evaluation of sodium aerosols released from a sodium fire event in SFRs or from a sodium handling facility, to determine the aerosol concentration and chemical species in the downwind direction, in particular, the chemical species is found to be bi-carbonate reducing the chemical hazard to greater extent. A model shall be applied to the site specific condition to predict the sodium aerosol concentration and deposition for any sodium fire incidents and subsequent release of aerosols.